Socioeconomic Impact of Mining on Local Communities in Africa - World Bank (Washington, DC, 2015)
For more than a decade, Africa has enjoyed a mineral boom. is the growth mostly happening in isolated places, sectors and periods? The approach adopted in this study is two-pronged. First, through case studies, including the results of fieldwork, mining’s impacts are examined in a country-specific context for each of three countries, Ghana, Mali, and Tanzania; and second, a statistical analysis is used to test whether the indicators of welfare improve with proximity to a mine.